Extracurricular Learning of Dance with Local Wisdom Basis - Muhammad, Fan Naa Na; Rohidi, Tjetjep Rohendi; Hartono, Hartono (Universitas Negeri Semarang, 2017)
Indonesia’s education system directs that the curriculum of every education level should insert local wisdom education, especially in arts subject. Every area in Indonesia has various performing arts. One of the arts in Kendal is Barongan dance which is able to be used as the learning source. This research aims to analyse the extracurricular learning process with local wisdom materials in SMA PGRI 1 Kendal. This research was a qualitative research. The technique of data collection consists of observation, interview, and documentation. The technique of data analysis used data reduction, data delivery, and data verification. The result of the research showed that the learning consisted of three stages, the beginning, main materials, and closing. The steps were in line to Gagne’s theory of learning phases motivation, introduction, acquisition, performance, and feedback. The beginning consisted of motivation and performance. The main part included the knowledge and the performance. Meanwhile, the closing dealt with the performance and feedback. The learning process also involved interaction. The learning of extracurricular in SMA PGRI 1 Kendal used local wisdom of Barongan with materials focusing on developing the arts. The formation of the dance consisted of lampah seblak, sembahan, jengkeng manggut,menthang tangan, and loncat jaran.